Batch Electrocoagulation Process for Removal of Chromium from Tannery Wastewater (Journal of Engineering Science, 2021)
This study was aimed to investigate the chromium removal from the tannery wastewater through electrocoagulation. The zinc and copper plates were used as electrodes for the electrocoagulation process. The effectiveness of the electrocoagulation for chromium removal efficiency was examined investigating various parameters: applied voltage, time, and current density. In batch experiment, 500 mL chromium-containing wastewater was used for electrocoagulation. Chromium content in the raw wastewater and after treatment at optimized conditions was 340.1 and 6.9 mg/L, respectively. The efficiency of chromium removal and reduction of biochemical oxygen demand (BOD) was at 98.0 and 64.6%, accordingly. Although total dissolved solids (TDS) was slightly increased. The increment of current density enhances forming zinc hydroxide which causes the damage of electrodes. Electrocoagulation is an effective technique to remove chromium from the wastewater especially from the tannery wastewater.Journal of Engineering Science 12(1), 2021, 29-34